2012
DOI: 10.1108/09564231211269838
|View full text |Cite
|
Sign up to set email alerts
|

Exploring internal mechanisms forming customer servicescape experiences

Abstract: PostprintThis is the accepted version of a paper published in Journal of Service Management. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the original published paper (version of record):Pareigis, J., Echeverri, P., Edvardsson, B. (2012) Exploring internal mechanisms forming customer servicescape experiences. Journal of Service Abstract:Purpose -The aim of this paper is to explore customer interactions with servicescapes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 45 publications
2
72
0
Order By: Relevance
“…Thus, the inter-subjective (i.e., mutual or dyadic co-creation between two and more customers) and collective (i.e., co-creation experiences shared among a group of community of customers) value dimensions also need to be explored (Edvardsson et al, 2011;Pareigis et al, 2012;Voima et al, 2010).…”
Section: Customer-dominant Logic and Value Formationmentioning
confidence: 99%
“…Thus, the inter-subjective (i.e., mutual or dyadic co-creation between two and more customers) and collective (i.e., co-creation experiences shared among a group of community of customers) value dimensions also need to be explored (Edvardsson et al, 2011;Pareigis et al, 2012;Voima et al, 2010).…”
Section: Customer-dominant Logic and Value Formationmentioning
confidence: 99%
“…Servicescapes are particularly important in environments where there is limited or no interaction with employees and the customer spends considerable time (Hightower, Brady, & Baker, 2002). Servicescapes not only influence the customer' value creation, but also have an impact on their future purchasing and consumption behavior (Pareigis et al, 2012). This is particularly true in experience-centric service organizations (Voss, Roth, & Chase, 2008).…”
Section: The Role Of Servicescape As a Driver Of Customer Experiencementioning
confidence: 99%
“…Besides enabling service operations, servicescapes serve as stimuli themselves, by providing cues (Pine & Gilmore, 1998) that create, influence, and enable the experience (Sandström, Edvardsson, Kristensson, & Magnusson, 2008). Servicescapes not only influence the customer' value creation, but also have an impact on their future purchasing and consumption behavior (Pareigis, Echeverri, & Edvardsson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study addresses a theoretical gap, showing that place attachment is a significant partial mediator of local residents' value cocreation behaviors, which impacts their subjective wellbeing. While studies have asserted that customer value cocreation behaviors are essential for driving service sustainability (Chou & Yuan, 2015;Edvardsson, Tronvoll, & Gruber, 2011;Pareigis, Echeverri, & Edvardsson, 2012), there has been little research for this, nor into how to better drive customer value cocreation behaviors. Our study showed that festival environmental cues and place attachment are both important determinants of local residents' value cocreation behavior; however, a direct and indirect effect of festival environmental cues through place attachment on value cocreation behavior should also be considered.…”
Section: Hypothesis Testing: Relation Of Festival Environmental Cuesmentioning
confidence: 99%